2017
DOI: 10.1002/cb.1658
|View full text |Cite
|
Sign up to set email alerts
|

Religious heterogeneity of food consumers: The impact of global markets upon methods of production

Abstract: The production and distribution of food is a topic of perennial interest. Specific concern arises over the provision of foods that have been prepared in accordance with religious requirements because they place additional demands and constraints upon methods of food production and distribution. This paper explores the attitude of consumers towards the method of production of food that has been prepared in accordance with the requirements of their own and other faiths. Consumer's gender, age, education level, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Prior research has shown that religion's influence on consumer behavior is wide reaching. Religion has been shown to influence consumers' switching tendencies (Choi, 2010), consumption activities in each life stage (Moschis & Ong, 2011), response to advertising tactics (Parry, Jones, Stern, & Robinson, 2013; Zwick & Chelariu, 2006), product risk perceptions (Baazeem, Mortimer, & Neale, 2016), morally relevant behavior (Arli & Pekerti, 2017; Dagher & Itani, 2014), and food consumption (White, Samuel, Zhou, Razak, & Thomas, 2018).…”
Section: Religion Consumers' Sense Of Belonging and Product Evaluatmentioning
confidence: 99%
“…Prior research has shown that religion's influence on consumer behavior is wide reaching. Religion has been shown to influence consumers' switching tendencies (Choi, 2010), consumption activities in each life stage (Moschis & Ong, 2011), response to advertising tactics (Parry, Jones, Stern, & Robinson, 2013; Zwick & Chelariu, 2006), product risk perceptions (Baazeem, Mortimer, & Neale, 2016), morally relevant behavior (Arli & Pekerti, 2017; Dagher & Itani, 2014), and food consumption (White, Samuel, Zhou, Razak, & Thomas, 2018).…”
Section: Religion Consumers' Sense Of Belonging and Product Evaluatmentioning
confidence: 99%
“…However, the absence of a univocal definition was more surprising. Halal is a certification that follows rules not based on health and hygiene standards but on religious commandments (Thomas et al 2017;White et al 2018White et al , 2021. The largest consumers of halal products are Muslims, who currently constitute 24% of the world's population and account for a market share of $1.2 trillion with an annual growth of 8.5%.…”
Section: Defining Certification Within the Agri-food Fieldmentioning
confidence: 99%
“…Religion serves as a source of core values for over 80% of consumers worldwide (Hackett & McClendon, 2017), with prior research showing consistent influences of such religious values on consumption behavior (cf., Arli & Pekerti, 2017; Baazeem, Mortimer, & Neale, 2016; Casidy & Arli, 2018; Geiger‐Oneto & Minton, 2019; Minton, 2018; Minton et al, 2016; Moschis & Ong, 2011; G. R. T. White, Samuel, Zhou, Razak, & Thomas, 2018; Zwick & Chelariu, 2006). This relationship fits with belief congruence theory, which establishes that consumers seek to act in ways that align with their core values and beliefs (Rokeach, 1960; Rokeach & Rothman, 1965).…”
Section: Religiosity's Influence On Luxury Disposalmentioning
confidence: 99%